2017
DOI: 10.1007/s00248-017-1075-y
|View full text |Cite
|
Sign up to set email alerts
|

Dual “Bacterial-Fungal” Symbiosis in Deltocephalinae Leafhoppers (Insecta, Hemiptera, Cicadomorpha: Cicadellidae)

Abstract: The symbiotic systems (types of symbionts, their distribution in the host insect body, and their transovarial transmission between generations) of four Deltocephalinae leafhoppers: Fieberiella septentrionalis, Graphocraerus ventralis, Orientus ishidae, and Cicadula quadrinotata have been examined by means of histological, ultrastructural, and molecular techniques. In all four species, two types of symbionts are present: bacterium Sulcia (phylum Bacteroidetes) and yeast-like symbionts closely related to the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…In the classic extensive histological surveys by German microbiologists ( 1 , 44 , 45 , 89 , 90 ), a comprehensive study detected fungal symbionts in as many as 237 (64%) of 370 species of plant-sucking hemipteran insects representing the Auchenorrhyncha (cicadas, spittlebugs, leafhoppers, treehoppers, planthoppers, etc.) ( 44 ), and recent studies, including this study, have shown that some of them are Ophiocordyceps -allied fungal symbionts ( 33 , 35 , 37 39 , 67 , 70 ). Here, we point out that such dynamic symbiont recruitment from fungal parasites may be taking place in diverse insects more generally than previously envisaged.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…In the classic extensive histological surveys by German microbiologists ( 1 , 44 , 45 , 89 , 90 ), a comprehensive study detected fungal symbionts in as many as 237 (64%) of 370 species of plant-sucking hemipteran insects representing the Auchenorrhyncha (cicadas, spittlebugs, leafhoppers, treehoppers, planthoppers, etc.) ( 44 ), and recent studies, including this study, have shown that some of them are Ophiocordyceps -allied fungal symbionts ( 33 , 35 , 37 39 , 67 , 70 ). Here, we point out that such dynamic symbiont recruitment from fungal parasites may be taking place in diverse insects more generally than previously envisaged.…”
Section: Resultsmentioning
confidence: 50%
“…Mycologists have described Ophiocordyceps and allied fungi as insect parasites, including many cicada-parasitizing species ( 56 , 93 96 ). Recent molecular phylogenetic approaches have identified some of the yeast-like fungal symbionts of insects as close relatives of the Ophiocordyceps entomopathogens ( 25 , 33 , 35 , 37 39 , 65 – 70 ). Recent genomic approaches to the insect-associated microbial communities have uncovered many striking cases of drastic size reduction and extreme metabolic streamlining in ancient bacterial symbiont genomes, some of which look like they are almost going beyond the limit of being able to sustain basic cellular functioning ( 19 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other rice planthoppers, the WBPH harbors intracellular yeast-like symbionts (YLS) in the fat body [3]. YLS occur not only in planthoppers but also in some aphids, scale insects, leafhoppers and cicadas [4][5][6]. The diversity of YLS in rice planthoppers has been recently demonstrated [7][8][9], and has been found to be altered in response to insecticides and environmental factors [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there are many cases in which YLS phylogenetically related to the entomopathogenic genus Ophiocordyceps (Ascomycota: Sordariomycetes: Hypocreales) have joined or replaced Sulcia and/or its bacterial partner. Thus, Sulcia has been replaced in some young lineages of Delphacidae planthoppers (Fulgoroidea) [107]; neither Vidania nor Sulcia were found in some young lineages of family Delphacidae where a vertically transmitted YLS was found [107,108]; and the same kind of YLS was found in some leafhoppers of subfamilies Deltocephalinae [109,110,111] and Ledrinae [112], whether replacing Nasuia or in an intermediate stage in which both Nasuia and the YLS coexist with Sulcia . In addition, many independent cases of Hodgkinia replacement have been found in several tribes of two cicadidae subfamilies; in fact, it is possible that repeated Hodgkinia -fungus and fungus–fungus replacements had occurred [85].…”
Section: The Case Of Cicadas and Relatives: Sulcia And Its Multiplmentioning
confidence: 99%